A randomised controlled trial of 1- versus 2-day per week formats of Nordic hamstring training on explosive athletic tasks in prepubertal soccer players - Abdelkader, M.; Hammami, R.; Drury, B.; Clark, N.; Sandercock, G.; Shaw, I.; Shaw, B. S.; Chortane, S. G.; Moran, J. (Journal of Sports Sciences, 2022)
This randomised controlled trial examined the effect of volume-equated programmes of Nordic hamstring exercise (NHE) training, executed at frequencies of 1- or 2-days per week, on explosive athletic tasks (30 m sprint, 15 m manoeuvrability and standing long jump [SLJ]) in male youth soccer players (mean age: 10.3 ± 0.5 years). Players were divided into an experimental group (n = 31) which was further subdivided into 1-day (n = 16) and 2-days (n = 15) per week training conditions, and a control group (n = 14). There were significant group-by-time interactions for 30-m sprint (p < 0.001, d = 0.6), SLJ (p = 0.001, d = 1.27) and 15 m manoeuvrability (p < 0.001, d = 0.61). The experimental group demonstrated small to moderate effect sizes in 30-m sprint (d = 0.42, p = 0.077), SLJ (d = 0.97, p < 0.001) and 15 m manoeuvrability (d = 0.61, p < 0.001). The control group showed small significant performance decrements or no change in these variables. There were no significant differences between the 1-day and 2-day training groups. In two of the three tests (30 m sprint, SLJ) the 2-day group demonstrated larger effect sizes. The NHE enhances explosive athletic task performance in prepubertal youth soccer players and there may be only small advantages to spreading training over two days instead of one.